Translation of knowledge in the Implementation of the nursing process in a neonatal unit (Research, Society and Development, 2021)
The objective of this study is to socialize the professional experience of implementing the nursing process in a neonatal care unit. This is an experience report of the implementation of the nursing process in a neonatal care unit of a federal hospital in Rio de Janeiro, which took place from May 2016 to December 2020, using the knowledge translation technique. The implementation was carried out in three stages: sensitization of the team and presentation of the form with three phases of the nursing process (history, diagnoses and nursing interventions); remaking of the form for the five phases of the nursing process and improvement of the form, allowing the inclusion of medicine scheduling and optimization of filling time. This sequence enabled the full implementation of the nursing process, adding improvements to the nursing records and enabling the qualification of the care provided. The implementation of the nursing process represents an excellent care management tool, identifying the individual needs of newborns and consequently qualifying care.